107k views
0 votes
6x-y=-23 8x+3y=-9 Substition method (Show it step by step please!)

User Percy Vega
by
6.1k points

1 Answer

1 vote

Answer:

solution is (- 3, 5 )

Explanation:

given the 2 equations

6x - y = - 23 → (1)

8x + 3y = - 9 → (2)

rearrange (1) expressing y in terms of x

y = 6x + 23 → (3)

Substitute y = 6x + 23 into (2)

8x + 3(6x + 23 ) = - 9

8x + 18x + 69 = - 9

26x + 69 = - 9 ( subtract 69 from both sides )

26x = - 78 ( divide both sides by 26 )

x = - 3

substitute x = - 3 into (3)

y = (6 × - 3 ) + 23 = - 18 + 23 = 5

solution is (- 3, 5 )


User Nitro Zark
by
6.2k points